Rapid synthesis of cesium-doped hydroxyapatite nanorods: characterisation and microbial activity. (18th August 2019) - AL-Wafi, Reem; Al-Ghamdi, Attieh A.; Jafer, Rashida; Al-Judaibi, Awatif A.; Al-Ghamdi, Maryam A.; Yahia, I. S.; Albulym, Obaid; El-Naggar, A. M.
ABSTRACT: Rapid synthesis of cesium-doped hydroxyapatite (Ca10 (PO4 )6 (OH)2, (HAp)) by rapid microwave synthesis technique is reported. The crystal, chemical, and dielectric properties, along with the phase composition and morphology were investigated. SEM study proved successful synthesis of HAp nanorods. The dielectric properties were affected by the doping amount of Cs-ions in HAp. The values of crystallinity degree at different concentrations of Cs-ions were decreased on increasing the Cs content. The antimicrobial activities of Cs-doped HAp showed high effects of growth inhibition on Staphylococcus aureus, S. saprophyticus, Escherichia coli, Haemophilus influenza, Candida albicans, and C. tropicalis . The concentration of 0.32 Cs-doped HAp has the high inhibition effect against S. aureus with the percentage of inhibition to 88.89%. The microbial inhibition growth reflected on the MICs and MBCs and MFCs. This newly designed Cs-doped HAp can be applicable in wide scales biomedical applications such as bone cement engineering and antimicrobial agents.